Impact of Monetary Policy on Bank Credit in Nigeria - Ademokoya, Alade Ayodeji; Sanni, Mubaraq; Oke, Lukman Adebayo; Abogun, Segun (Universitas Syiah Kuala, 2020)
Objective The aim of this study is to examine the impact of monetary policy on credit creation ability of banks in Nigeria. Specifically, it investigates the impact of monetary policy rate, money supply, liquidity ratio, and change in maximum lending rate on bank credit in Nigeria.Design/methodology A monthly time series data from 2007-2019 were sourced from the Central Banks of Nigeria statistical bulletin. The sourced data was subjected to multiple regression analysis using the fully modified ordinary least square regression to estimate the parameters of the model.Results Findings reveal that money supply significantly and positively influence bank credit in Nigeria; while liquidity ratio significantly but negatively influence bank credit in Nigeria. On the contrary, monetary policy rate and maximum lending rate were found not to significantly affect bank credit in the case of Nigeria.Policy Recommendation - Study therefore, recommend that monetary authorities especially, the Central Bank of Nigeria should pay more attention to lowering the liquidity ratio while increasing money supply in order to engender banks credit creation ability and further stimulate the Nigerian economy for growth.